Quantitative ST-depression in acute coronary syndromes: the PLATO electrocardiographic substudy - Armstrong, Paul W.; Westerhout, Cynthia M.; Fu, Yuling; Harrington, Robert A.; Storey, Robert F.; Katus, Hugo; James, Stefan; Wallentin, Lars (The American journal of medicine, 2013)
Background - We evaluated whether electrocardiogram (ECG) characteristics were aligned with clinical outcomes and the effect of ticagrelor within the diverse spectrum of non-ST-elevation acute coronary syndrome patients enrolled in the PLATelet inhibition and patient Outcomes (PLATO) trial. - Methods - There were 8884 PLATO patients who had baseline ECGs assessed by a core laboratory; of these, 4935 had an ECG at hospital discharge that also was assessed. Associations with study treatment on vascular death or myocardial infarction within 1 year were examined. - Results - At baseline, most patients had either no or ≤0.5 mm of ST-segment depression (57%); 26% had 1.0 mm, and 17% had more extensive depression (>1.0 mm). Across the baseline ST-segment depression strata, there was a consistent treatment benefit with ticagrelor versus clopidogrel on vascular death/myocardial infarction. The extent of residual ST-segment depression at discharge was similar in the treatment groups, and the treatment effect did not differ by the extent of discharge ST-segment depression. There was a progressive increase in vascular death/myocardial infarction with increasing extent of baseline ST-segment depression (1.0 mm [vs no/0.5 mm]: hazard ratio [HR] 1.22; 95% confidence interval [CI], 1.03-1.45; >1.0 mm: HR 1.49; 95% CI, 1.24-1.78; P <.001) and at discharge (HR 1.28; 95% CI, 1.02-1.61; HR 2.13; 95% CI, 1.54-2.95; P <.001). - Conclusion - The treatment effect of ticagrelor among non-ST-segment-elevation acute coronary syndrome patients was consistently expressed across all baseline ST-segment depression strata. There was no indication of an anti-ischemic benefit of ticagrelor as reflected on the discharge ECG. Our data affirm the independent prognostic relationship of both baseline and hospital discharge ST-segment depression on outcomes within 1 year in non-ST-segment-elevation acute coronary syndrome patients.
Gesehen am 26.10.2020